Insight into chromatin compaction and spatial organization in rice interphase nuclei - Doležalová, Alžběta; Beránková, Denisa; Koláčková, Veronika; Hřibová, Eva (Frontiers in Plant Science, 2024)
Chromatin organization and its interactions are essential for biological processes, such as DNA repair, transcription, and DNA replication. Detailed cytogenetics data on chromatin conformation, and the arrangement and mutual positioning of chromosome territories in interphase nuclei are still widely missing in plants. In this study, level of chromatin condensation in interphase nuclei of rice (Oryza sativa) and the distribution of chromosome territories (CTs) were analyzed. Super-resolution, stimulated emission depletion (STED) microscopy showed different levels of chromatin condensation in leaf and root interphase nuclei. 3D immuno-FISH experiments with painting probes specific to chromosomes 9 and 2 were conducted to investigate their spatial distribution in root and leaf nuclei. Six different configurations of chromosome territories, including their complete association, weak association, and complete separation, were observed in root meristematic nuclei, and four configurations were observed in leaf nuclei. The volume of CTs and frequency of their association varied between the tissue types. The frequency of association of CTs specific to chromosome 9, containing NOR region, is also affected by the activity of the 45S rDNA locus. Our data suggested that the arrangement of chromosomes in the nucleus is connected with the position and the size of the nucleolus.